Biomarkers in Nonalcoholic Fatty Liver Disease - Manuela G Neuman; Lawrence B Cohen; Radu M Nanau (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is a chronic liver condition characterized by insulin resistance, type 2 diabetes and fat accumulation in the liver that may cause hepatic inflammation and progressive scarring leading to nonalcoholic steatohepatitis (NASH) and irreversible liver damage (cirrhosis). As a result, there has been increased recognition of the need to assess and closely monitor individuals for risk factors of components of NAFLD and NASH, as well as the severity of these conditions using biomarkers.